Nepal and COVID-19: A strange case and the Dilemma - Thapa, Amit (Nepal Journal of Neuroscience, 2020)
COVID-19 caused by SARS-CoV-2 started as an outbreak in Wuhan, China in December 2019. Despite strict measures put up by China, its silent but highly contagious nature led to widespread dissemination which made World Health Organization (WHO) declare it as a global pandemic on 11 March 2020. With 152,523 people dying among 2,347,060 affected in 213 countries and territories due to the disease, nations are fighting to “flatten the curve of epidemic. The situation in Nepal has been rather strange. Due to its geographical proximity to China and porous borders, WHO quickly declared it a high-risk country for COVID-19, however, only few cases had been reported till date with no record of local transmission (except for one with direct contact) even after testing 8081 samples. It appears as if Nepal has been able to keep the pandemic in early phase for this long!